Gendered Competitive Practices in Economics. A Multi-Layer Model of Women's Underrepresentation - Theresa Hager; Stephan Pühringer (Johannes Kepler University Linz, Research Project SPACE - Spatial Competition and Economic Policies, 2023)
Economics holds a unique position in terms of the severity and persistence of gender imbalances and the underrepresentation of female researchers within the social sciences. There exist various reasons for this fact, as well as a variety of channels through which these imbalances are perpetuated. To this end, there has not been a comprehensive review of the existing and well-researched levels of this underrepre-sentation. By systematically reviewing the literature on the facts and reasons for the low proportion of women in the profession and structuring them in our multi-level model, we not only make the multitude of channels visible but can also analyze their interplay. Moreover, we argue that efforts to address women's underrepresentation are impeded because economics as a discipline is particularly susceptible to competitive evaluation and selection practices. Men and women perceive, perform in, and make sense of competitive processes in their own ways, so that men, through their socialization as competitive selves, are more likely to succeed in an academic system heavily based on competition and rankings; women, in this case, are endowed with an inappropriate set of competitive strategies and interpretations that, nevertheless, ultimately inform their academic practices. Enriching our multi-level model with this perspective on gendered competitive practices in academia, allows us to offer a novel contribution to the debate on the causes of the persistent gender imbalance in the field. Drawing from feminist stand-point theory, we argue that such an endeavor is not only important, and interesting in its own right, but also highly relevant to the reproduction of gender imbalances and gender discrimination in society at large; if a diversity of views and opinions is not represented within its halls, economics runs the risk to inform policy lopsided. More precisely, we argue that our result has some nontrivial implications given the rise of competitive formats in academia and thus is particularly alarming for science policies aiming at gender balances in academia.
Keywords: 330; competition; Gender in economics; female underrepresentation; academia